Evidence-Based Validation of Hemolysis Index Thresholds by Use of Retrospective Clinical Data. (15th January 2020) - Mays, James A; Greene, Dina N; Merrill, Anna E; Mathias, Patrick C
Abstract: Background: Semiquantitative hemolysis indices (HIs) are used by chemistry analyzers to measure sample integrity, but there is little standardization in HI reporting or validation of analyte-specific HI flagging. Additional methods of HI threshold validation are needed. Methods: We retrospectively queried serum and plasma potassium measurements, HIs, and contemporaneous whole blood potassium measurements. Serum and plasma values were compared to whole blood values drawn within 6 h (n = 6422 pairs), and discrepancies between values were compared across HIs. We also retrieved orders of potassium-lowering medications occurring shortly after release of potassium results from hemolyzed samples. Results: While nonhemolyzed samples showed high agreement, a significant percentage of released hemolyzed samples (36.1% of the most hemolyzed group) were discrepant by 1 mEq/L or more. In total, 15.5% of patients with an order from the hyperkalemia order set had the order after a hemolyzed value; the majority of those patients (42 of 46; 91.3%) received a potassium-lowering medication, most of whom did not have a redraw before drug administration. Conclusions: Retrospective review of discrepancies identified marked inconsistencies among higher HI samples and identified opportunities for improving the laboratory reporting policy, offering a clinical validation of the HI thresholds for potassium. Clinicians generally treated patients with hemolyzed samples, underscoring the importance of maintaining sample quality.